Structural, thermal, in vitro degradation and cytocompatibility properties of P2O5-B2O3-CaO-MgO-Na2O-Fe2O3 glasses - Zhu, Chenkai; Ahmed, Ifty; Parsons, Andy; Hossain, Kazi Md Zakir; Rudd, Chris D.; Liu, Jingsong; Liu, Xiaoling (Elsevier, 2017)
Borophosphate glasses with compositions of (48 − x)P2O5-(12 + x)B2O3-14CaO-20MgO-1Na2O-5Fe2O3 (where x = 0, 3, 8 mol%) were prepared via a melt-quenching process. The effects of replacing P2O5 with B2O3 on the structural, thermal, degradation properties and cytocompatibility were investigated. Fourier transform infrared (FTIR) spectroscopy analysis confirmed the existence of BO3 triangular units and BO4 tetrahedral units within all the glasses with an increase of B/P ratio from 0.25 to 0.5. The BO4 units within the glass structure were observed to cause an increase in density (ρ) as well as glass transition (Tg) temperature and to decrease the crystallisation temperature (Tc). A decrease in thermal stability which indicated by process window was also observed in the case of substitution of P2O5 with B2O3. Degradation analysis of the glasses indicated that the dissolution rate increased with the addition of B2O3. The decrease in the thermal stability and chemical durability were attributed to the increase of BO3 units, which could increase crystallisation tendency and be easily hydrolysed by solution. The effect of boron addition on the cytocompatibility of the glasses was analysed using Alamar Blue and alkaline phosphatase (ALP) assays and DNA quantification. MG63 osteosarcoma cells cultured in direct contact with the glass samples surface for 14 days showed better cytocompatibility, compared to the tissue culture plastic (TCP) control group. In summary, the glass formulation with 12 mol% B2O3 presented the best cytocompatibility and thermal stability, thus could be considered for continuous fibre fabrication in future research and downstream activities.